The Effectiveness of Using “Lexie Limitless” YouTube Channel in Improving Speaking Skill - Wibowo, Rachmat Ari; Sulistyorini, Dwi (English Language and Education Spectrum, 2025)
The structures of spoken language are quite different from the written language, which they have time to plan, edit and correct what they produce. Our personality, ourselves image, our knowledge of the world and our ability to express our thoughts are reflected in our speaking performance. In Ivet University, where the research was taken place, I found problems of learning English speaking skill that come from students, teacher, strategy, and facility of learning. Youtube can be a learning resource and learning media that can meet the demands of the digital generation. Youtube can increase interest and support the learning styles of the digital generation. Youtube also offers learning experiences with new technologies that will be useful when they graduate. This research uses descriptive qualitative method as the method of the research. The analysis conducted to the first semester students of Geography Education Department of Ivet University, The aim of this research was to know the effectiveness of using YouTube video in developing students' speaking skills. The assessment was in form of speeches in front of the classroom. There are 25 studentss for the 1st semester of 2025, all of whom are internet generations. The research lasted for 1 month which consisted of 2 meetings per week. In the Lexie Limitless Youtube Channel it is packaged attractively and in each video there are English subtitles that can be used by studentss to learn about the formation of English sentence structures, learn about pronunciation, intonation, grammar, etc. The results showed that videos on YouTube can be used as a learning medium, and the studentss enjoy learning with it.